Study of knowledge, attitude, practices regarding PPIUCD among antenatal women at a tertiary care centre in Northern India - Asnani, Mona; Agarwal, Anjoo; Singh, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: PPIUCD has been introduced in the national family welfare program since March 2010 in several states. AN IUCD can be inserted in 48 hours postpartum, referred to here as postpartum intrauterine contraceptive device. This study was done to assess the Knowledge, attitude and practice of postpartum Intrauterine contraceptive device in antenatal patients at a tertiary care centre in Northern India. Methods: This is a questionnaire based cross sectional observational study including 350 antenatal women attending antenatal OPD over a period of 6 months. Results: Out of these 350 women, 126 women (36%) had knowledge of PPIUCD. only 30 % of women had previous knowledge about PPIUCD however only 10 % of women practiced it in the past. After appropriate counselling 18% of women agreed for insertion of PPIUCD after this delivery. Conclusions: The study concludes that the antenatal women had poor knowledge regarding PPIUCD. Practices were even worse. This might be attributed to low education , refusal by family especially male partner, and religious beliefs. But once appropriate knowledge and information is provided, attitude gradually changes.